Mentoring model for undergraduate teaching in production engineering - Côrtes, Andresa Deoclídia Soares; Junior, Antônio Henriques de Araújo; Marins, Fernando Augusto Silva; Sabbadini, Francisco Santos; Barros, José Glênio Medeiros de; Abreu, Laura Dutra de; Almeida, Maria da Glória Diniz de; Matias, Nelson Tavares; Sampaio , Nilo Antônio de Souza; Bittar, Rita de Cássia da Silveira Marconcini (Seven Editora, 2023)
The goal of this thesis is to present a mentoring program for undergraduate teaching regarding Industrial Engineering in Brazilian public universities in industrial student training period. The proposed program is based on previous works available in specialized literature, regarding mentoring and industrial engineering teaching. The employed research methodology was of qualitative applied nature, through a research-action approach. To test the coherence of the questionnaire respondents, which was applied to mentors and mentees in the theme of mentoring in the industrial sector, the α-Cronbach test was adopted. And aiming to validate the proposed program it was applied a statistical test of comparison between proportions. Among protégés, 85% confirmed that the project has made a difference in production engineering education during their trainee period, while mentors reinforced that 98% of mentees had their industrial engineering competencies and skills developed. Amid program limitations, we identified that there is a lack of mentor's availability for formal training, and to minimize this problem, the proposed program has a detailed procedure to facilitate its use. The main contribution of this thesis regards its pioneer aspect in creating a mentoring program for production engineering teaching, bringing universities closer to manufacturing businesses, during the student training period. DOI:https://doi.org/10.56238/uniknowindevolp-113